1994
DOI: 10.1007/bf01651014
|View full text |Cite
|
Sign up to set email alerts
|

An isolated dissecting: aneurysm of the superior mesenteric artery: report of a case

Abstract: We report herein the case of a 56-year-old man found to have an isolated dissecting aneurysm of the superior mesenteric artery (SMA) after he presented with a 3-day history of postprandial epigastralgia of sudden onset. An echogram showed marked dilatation of the SMA and a high level of peripheral echoes in a linear fashion within its lumen. A thin-section contrast enhanced computed tomography revealed a thin flap, separating two distinct well-enhanced lumina. Angiography confirmed the presence of a localized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 11 publications
0
20
0
1
Order By: Relevance
“…Some authors insist that anticoagulation therapy is valid and should be a mainstay for the conservative management of SIDSMA after the first successful treatment with intravenous heparin (Ambo et al). 14,21,23 This opinion has been strengthened by the experience with treatment of spontaneous dissection of the carotid artery, where anticoagulation is effective in preventing the formation of the thrombus. 28 Considering the aforementioned treatment objectives of the SIDSMA and the previous reports 3,10 that have described the progression of disease and aneurysmal dilatation in some cases despite the administration of chronic anticoagulation therapy, anticoagulation or antiplatelet therapy could not be the optimal treatment for SIDSMA.…”
Section: Resultsmentioning
confidence: 94%
“…Some authors insist that anticoagulation therapy is valid and should be a mainstay for the conservative management of SIDSMA after the first successful treatment with intravenous heparin (Ambo et al). 14,21,23 This opinion has been strengthened by the experience with treatment of spontaneous dissection of the carotid artery, where anticoagulation is effective in preventing the formation of the thrombus. 28 Considering the aforementioned treatment objectives of the SIDSMA and the previous reports 3,10 that have described the progression of disease and aneurysmal dilatation in some cases despite the administration of chronic anticoagulation therapy, anticoagulation or antiplatelet therapy could not be the optimal treatment for SIDSMA.…”
Section: Resultsmentioning
confidence: 94%
“…This is justified on the basis of known spontaneous regression of certain SSDs, 23 the infrequent occurrence (one reported case) of rupture, 8 and the documented tendency of chronic descending aorta and descending aortic branch dissections to demonstrate slow rather than abrupt or rapid change, permitting effective serial imaging in followup. 41,42 In contrast, immediate operative or endovascular intervention is warranted if any of the previously documented adverse sequelae of SSD are believed to be imminent.…”
Section: Discussionmentioning
confidence: 95%
“…Initial cases were treated successfully with open resection and either bypass or transposition of the distal artery. 3,4 In 1994, Ambo et al 23 reported the successful, non-operative (conservative) management of an SMA dissection with subsequent thrombosis of the false lumen and preservation of distal flow. However, this approach has not proven to be universally successful.…”
Section: Discussionmentioning
confidence: 98%
“…Of the 25 Anticoagulation therapy has since become the mainstay for the conservative treatment of SMA dissections and has been associated with improved results. Ambo et al 33 were the first to successfully treat a patient conservatively with bowel rest and intravenous heparin therapy. Since this initial report, 22 similar cases have been described in the literature, with a successful outcome in 14 patients.…”
Section: Discussionmentioning
confidence: 98%